2021
DOI: 10.1021/acs.est.0c03890
|View full text |Cite
|
Sign up to set email alerts
|

Durable Goods Drive Two-Thirds of Global Households’ Final Energy Footprints

Abstract: Sustainability endorses high quality, long-lasting goods. Durable goods, however, often require substantial amounts of energy during their production and use-phase and indirectly through complementary products and services. We quantify the global household's final energy footprints (EFs) of durable goods and the complementary goods needed to operate, service and maintain durables. We calculate the EFs of 200 goods across 44 individual countries and 5 world regions for the period of 1995−2011. In 2011, we find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
(194 reference statements)
1
14
0
1
Order By: Relevance
“…Ref. 21 built a capital transaction matrix 𝐾 with the same dimensions as Z, from the vector f of year 2015. Once added to Z, this matrix allows to consider CFC not as a sub-share of Y (Fig.…”
Section: Capital Endogenizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Ref. 21 built a capital transaction matrix 𝐾 with the same dimensions as Z, from the vector f of year 2015. Once added to Z, this matrix allows to consider CFC not as a sub-share of Y (Fig.…”
Section: Capital Endogenizationmentioning
confidence: 99%
“…This approach makes it necessary to study sector-level energy intensities as a function of affluence, to better pinpoint how different consumption patterns lead to unequal energy use 17,18,19 . So far, only three studies 20,21,22 have carried out multi-sectoral and multi-regional comparisons of footprint energy intensities of goods and services. Oswald and colleagues 19 have calculated sectoral final energy intensities and concluded that higher-income individuals tend to buy goods that are more energy intensive.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second most important consumption category is Media and Communication accounting for 18-37% of the carbon footprint of manufacturing products. Some of the best strategies to reduce the carbon footprint of the manufactured products are a circular economy aimed at reduction of the ownership, an extension of the replacement cycle (more durable goods and better repair possibilities), and policies targeting inter-linkages between durables and complements [114,115]. The environmental certification also could help people to choose more environmentally friendly products seeking to reduce the environmental impact caused by consumption.…”
Section: Other Sectorsmentioning
confidence: 99%